Missed opportunities in family planning: process evaluation of family planning program in Omo Nada district, Oromia region, Ethiopia - Misganu Endriyas; Tefera Belachew; Berhane Megerssa (BMC, 2018)
Abstract Background Family planning (FP) program is a key program to avert unbalanced human population growth, maternal mortality, unintended pregnancy, unsafe abortion, sexually transmitted diseases and malnutrition. To address these aims, all services that clients receive must be of consistently high quality. So, services that clients receive should be monitored and evaluated. Methods Case study was carried out in January, 2011, in Omo Nada district, Oromia region. Data were collected using different data collection methods. Process of FP program was evaluated using Judith Bruce model. Geographical accessibility, availability of resources for service provision and technical compliance were assessed. Level of program implementation was measured using stakeholders' agreed indicators and judgment matrix. Results Though overall program implementation level was good and clients were satisfied, notable gaps observed were absence of crucial materials, poor provision of information in relation to method given, poor technical performance in following aseptic procedure, and poor integration of services. Conclusion Service provision should be monitored to maintain quality of service by integrating available services in resource limited setting.